In-between soil erosion and sustainable land management: climate aridity and vegetation in a traditional agro-forest system (Costiera Amalfitana, southern Italy). Issue 5 (2nd September 2016) - Savo, Valentina; Salvati, Luca; Caneva, Giulia
ABSTRACT: The delineation of bioclimatic areas is a key tool in informing sustainable land management strategies, especially in the light of climate change. It requires an in-depth analysis of climate data but also of the physical and biological factors that affect the distribution of natural vegetation. The present study applies an exploratory data analysis aimed at defining bioclimatic conditions in an area characterized by steep slopes and prone to soil erosion (Amalfi Coast, southern Italy). To this end, we analyzed long-term (1959–1999) monthly rainfall and temperature data measured at 28 gauging stations within the study area using a geographic information system and multivariate statistical tools. Then, we analyzed how the spatial distribution of rainfall and temperature data relates to topography, vegetation cover, and soil erosion. We also derived bioclimatic indicators from the geostatistical analysis. We then identify and comment on drawbacks found in the procedure used in the present study, discussing possible solutions to overcome such problems. We finally discuss the potential contribution of this study to the development of sustainable land management policies for socio-ecological systems with complex topography.